Patterns of Inter-Chromosomal Gene Conversion on the Male-Specific Region of the Human Y Chromosome - Trombetta, Beniamino; D’Atanasio, Eugenia; Cruciani, Fulvio (Frontiers in Genetics, 2017)
The male specific region of the human Y chromosome (MSY) is characterized by the lack of meiotic recombination and it has long been considered an evolutionary independent region of the human genome. In recent years, however, the idea that human MSY did not have an independent evolutionary history begun to emerge with the discovery that inter-chromosomal gene conversion can modulate the genetic diversity of some portions of this genomic region. Despite the study of the dynamics of this molecular mechanism in humans is still in its infancy, some peculiar features and consequences of it can be summarized. The main effect of inter-chromosomal gene conversion is to increase the allelic diversity of MSY by generating a significant excess of clustered SNPs (defined as groups of two or more SNPs occurring in close proximity and on the same branch of the Y phylogeny). On the human MSY, 13 inter-chromosomal gene conversion hotspots (GCHs) have been identified so far, involving donor sequences mainly from the X-chromosome and, to a lesser extent, from autosomes. Most of the GCHs are evolutionary conserved and overlap with regions involved in aberrant X-Y crossing-over. This review mainly focuses on the dynamics and the current knowledge concerning the recombinational landscape of the human MSY in the form of inter-chromosomal gene conversion, on how this molecular mechanism may influence the evolution of the MSY, and on how it could affect the information enclosed within a genomic region which, until recently, appeared to be an evolutionary independent unit.